Understanding contemporary China - Gamer, Robert E. (Lynne Rienner, 1999)
Understanding Contemporary China" offers undergraduates a coherent assessment of the most crucial issues affecting China today. Designed as a core text for "Introduction to Asia" or "Introduction to China" courses, it can also be used in a wide variety of discipline-oriented curriculums. Assuming no prior knowledge on the part of the reader, the book begins with an overview of China's geography and cultural history. The authors then provide a thorough treatment not only of the country's politics and economy, but also of demographic trends, environmental problems, family patterns, the role of women in development, and religion and cultural expression. Each chapter provides historical context, and each topic is covered with reference to the recent available scholarship. It reveals the complexity of China's challenges at the end of the 20th century and their global impact and the prospects for the future of the country.